Evaluación de Sostenibilidad Agroproductiva del CEASA bajo los Lineamientos de La FAO - Armas Achig, Edwic Raphael (2019)
In this research project, through the application of the methodology proposed by the FAO, a baseline about the current state of the agroproductive sector of the CEASA campus sustainability was established; this methodology is based on four axes that are: environmental integrity, economic resilience, good living and good governance. Sustainability has become a fundamental axis in all areas of production and the agroproductive sector is not the exception, this activity is, at different levels, one of the main economic and social axes of the country, the lack of related information to this topic represents a risk for its development. After the delimitation of the study area, in the course of approximately 6 months, in order to collect reliable information, the following were carried out: analysis of the state of biodiversity through direct observation of the environment; surveys and interviews to members of the administrative, labor and student staff of the institution; as well as water and soil studies. The information obtained was entered into the SAFA software, and a polygon that reflects the state of sustainability of the campus was generated. It was determined that, despite the fact that the sustainability polygon generated for the CEASA Campus's Agroproductive Sector shows a mainly positive result, there are some shortcomings, mainly the lack of written plans with objectives and temporary goals for the management of natural resources, accounting and energetics; the lack of documentation regarding the strategies implemented to mitigate the impacts caused, the conservation of ecosystems and species, and the recovery of soils. The information collected can be used to propose effective solutions that, after being applied, will allow improving the state of sustainability of the campus. It was concluded that the economic, social, environmental and productive aspects are intertwined and each one represents an important pillar for sustainability; the campus already has practices aimed at sustainability, it is necessary to polish them to reach the standards set by FAO and be recognized as a sustainable agroproductive sector; the basis on which work must be done to reach these standards, could be the generation of a holistic management plan.